Behind bars: letters from history's most famous prisoners - Drake, James; Smyth, Edward; Aitken, Jonathan (Letters for the Ages, 2024)
Letters for the Ages Behind Bars is a history of imprisonment told through the letters of people incarcerated over many centuries, for crimes committed or sometimes even for no reason at all. It is a story that runs from St Paul right up to the present day.The act of depriving someone of their liberty is one of humankinds most enduring responses to crime through history. What society has sought to achieve over the years by doing so has shifted across the centuries and there is now a variety of purposes: to express disapproval; for the purpose of straight-up punishment through the removal of freedom; to protect the general public; to rehabilitate, perhaps even to forget about those with whom we simply cannot cope. The letters assembled here come from all parts of the world, and from time immemorial: Thomas Cromwell, Mary Queen of Scots, Eamon De Valera, Al Capone, Martin Luther King and many more.These letters not only reveal what it is like to be behind bars, but raise issues that are still of pressing interest for us today - such as the death penalty, miscarriages of justice, redemption and social change. They shed light on a system which is primarily one of contradictions - there are letters which inspire, horrify, letters which awe and condemn - even letters which make you laugh or cry